A new species of Scutopalus (Acari: Cunaxidae: Cunaxoidinae) from Rio Grande do Sul State, Brazil with a key to world species - Rocha, Matheus Dos Santos; Skvarla, Michael Joseph; Ferla, Noeli Juarez (Zootaxa, 2013)
Scutopalus tomentosus sp. nov. is described and illustrated from Plantago tomentosa Lam. (Plantaginaceae) in a vineyard agroecosystem at Dois Lajeados county, State of Rio Grande do Sul, Brazil. This is the first species of this genus described from the Americas. A key to world species is included.